Regulation of arsenite oxidation by the phosphate two-component system PhoBR in Halomonas sp. HAL1 - Chen, Fang; Cao, Yajing; Wei, Sha; Li, Yanzhi; Li, Xiangyang; Wang, Qian; Wang, Gejiao (Frontiers in Microbiology, 2015)
Previously, the expression of arsenite [As(III)] oxidase genes aioBA was reported to be regulated by a three-component regulatory system, AioXSR, in a number of As(III)-oxidizing bacterial strains. However, the regulation mechanism is still unknown when aioXSR genes are absent in some As(III)-oxidizing bacterial genomes, such as in Halomonas sp. HAL1. In this study, transposon mutagenesis and gene knock-out mutation were performed, and two mutants, HAL1-phoR931 and HAL1-△phoB, were obtained in strain HAL1. The phoR and phoB constitute a two-component system which is responsible for phosphate (Pi) acquisition and assimilation. Both of the mutants showed negative As(III)-oxidation phenotypes in low Pi condition (0.1 mM) but not under normal Pi condition (1 mM). The phoBR complementation strain HAL1-△phoB-C reversed the mutants’ null phenotypes back to wild type status. Meanwhile, lacZ reporter fusions using pCM-lacZ showed that the expression of phoBR and aioBA were both induced by As(III) but were not induced in HAL1-phoR931 and HAL1-△phoB. Using 15 consensus Pho box sequences, a putative Pho box was found in the aioBA regulation region. PhoB was able to bind to the putative Pho box in vivo (bacterial one-hybrid detection) and in vitro (electrophoretic mobility gel shift assay), and an 18-bp binding sequence containing nine conserved bases were determined. This study provided the evidence that PhoBR regulates the expression of aioBA in Halomonas sp. HAL1 under low Pi condition. The new regulation model further implies the close metabolic connection between As and Pi.